Method for the production of pure and C-doped nanoboron powders tailored for superconductive applications. (28th September 2020) - Capra, Marco; Loria, Federico; Bernini, Cristina; Bovone, Gianmarco; Moros, Alice; Stöger-Pollach, Michael; Schachinger, Thomas; Bernardi, Johannes; Siri, Antonio Sergio; Vignolo, Maurizio
Abstract: The present paper describes the improvement of the performances of boron powder obtained applying the freeze-drying process (FDP) for the nanostructuration and doping of B2 O3, which is here used as boron precursor. After the nanostructuration process, B2 O3 is reduced to elemental nanoboron (nB) through magnesiothermic reaction with Mg. For this work, the usefulness of the process was tested focusing on the carbon-doping (C-doping), using Cblack, inulin and haemoglobin as C sources. The choice of these molecules, their concentration, size and shape, aims at producing improvements in the final compound of boron: in this case the superconductive magnesium diboride, which has been prepared and characterized both as powder and wire. The characteristics of B2 O3, B and MgB2 powder, as well as MgB2 wire were tested and compared with that obtained using the best commercial precursors: H. C. Starck micrometric boron and Pavezyum nanometric boron. Both the FDP and the magnesiothermic reaction were carried out with simplicity and a great variety of doping sources, i.e. elements or compounds, which can be organic or inorganic and soluble or insoluble. The FDP allows to produce nB suitable for numerous applications. This process is also very competitive in terms of scalability and production costs if compared to the via gas technique adopted by nanoboron producers currently available on the world market.